2014
DOI: 10.1002/uog.12519
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time elastography for assessment of uterine disorders

Abstract: Objectives Sonoelastography is an ultrasound-imaging

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 14 publications
3
52
1
3
Order By: Relevance
“…In a recent study, it was shown that elastography was able to identify clear discriminating characteristics of the uterus, fibroids, and adenomyosis, and elastographically based diagnoses were in excellent agreement with those of magnetic resonance imaging. 17 In another study, the authors concluded that elastography allows for the assessment of the presence of a uterine fibroid or adenomyosis and helps differentiate between both focal findings. 23 Interestingly, it was also shown that the stiffness of normal uterine tissue increased with age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, it was shown that elastography was able to identify clear discriminating characteristics of the uterus, fibroids, and adenomyosis, and elastographically based diagnoses were in excellent agreement with those of magnetic resonance imaging. 17 In another study, the authors concluded that elastography allows for the assessment of the presence of a uterine fibroid or adenomyosis and helps differentiate between both focal findings. 23 Interestingly, it was also shown that the stiffness of normal uterine tissue increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…Possible uses of elastography in obstetrics and gynecology include differential diagnosis of endometrial disorders, 8 prediction of preterm delivery, 9 12 and successful labor induction 13 16 . In a recently published study, it was shown that elastographically based diagnoses were in excellent agreement with those of magnetic resonance imaging for fibroids and adenomyosis 17 . Considering the fact that endometrial polyps derive from soft endometrial tissue, and submucosal fibroids are made of hard muscle and fibrous tissue, elastography seems a perfect tool for differentiating such intrauterine masses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intraabdominal lymph nodes have primarily been studied using endoscopic ultrasound with promising results [37]. Finally the uterus and adnexa have been studied looking for changes in uterine stiffness during pregnancy and for evaluation of fibroids, adenomyosis [38] and ovarian tumors [39]. Table 1 shows a rough comparison of strain elastography with shear wave elastography for abdominal applications.…”
Section: Elastography Using Dynamic Techniquesmentioning
confidence: 99%
“…It has already been demonstrated that elastography is useful in characterizing, on the one hand, various tumors such as breast, thyroid and prostate cancers; and on the other hand, lymph nodes and focal or diffuse liver diseases . This imaging technique has recently been released to the field of gynecology and obstetrics . In obstetrics, elastography was mainly used in the assessment of the cervix.…”
Section: Introductionmentioning
confidence: 99%